Cuidadores informais de idosos em pós-operatório de cirurgia de fêmur proximal: prevenção de novas quedas - Avila, Marla Andréia Garcia De [UNESP]; Pereira, Gilberto José Cação [UNESP]; Bocchi, Sílvia Cristina Mangini [UNESP] (ABRASCO - Associação Brasileira de Saúde Coletiva, 2015)
The objectives of this study were to investigate the sociodemographic characteristics of informal caregivers of elderly persons who had undergone surgery for hip fractures caused by a fall, explore the level of caregiver's knowledge regarding fall prevention, and assess the relationship between this knowledge and the use of preventative measures in practice. This investigation consists of a cross-sectional study using nonprobability sampling methods conducted over a period of 12 months and involving 89 caregivers. The majority of caregivers were female (76.4%) and sons or daughters of the patients (64%). Environmental modification was the predominant preventative measure used by caregivers (88.2%). 58.1% of caregivers believed it was possible to prevent falls in the elderly and there was a significant association (p = 0,002) between believing it was possible to prevent falls and carrying out modifications in the home and/or to the daily routine of the older person. Informal caregivers with wide or partial knowledge of fall prevention put preventative measures into practice. These findings demonstrate that the number of falls among older persons could be significantly reduced if health care programmes widened their actions to include the guiding principles of the WHO falls prevention model.

Os objetivos foram caracterizar sociodemograficamente os cuidadores informais de idosos vítimas de queda seguida por fratura de fêmur proximal e verificar o conhecimento mínimo que possuíam acerca da prevenção de novas quedas, assim como caracterizar a relação entre esse conhecimento e o emprego de medidas preventivas. Trata-se de estudo transversal, com amostragem intencional, realizado em 12 meses, incluindo 89 cuidadores. Predominaram cuidadores do sexo feminino (76,4%) e filhas(os) (64%). A modificação ambiental foi a medida preventiva predominante apontada por eles (88,2%). Houve associação significativa (p = 0,002), entre os 58,1% dos cuidadores que achavam ser possível prevenir quedas e os relatos sobre mudanças na casa e/ou rotina do idoso. Observou-se que cuidadores informais que apresentavam conhecimento sobre prevenção de quedas em idosos, mesmo que incompletos, empregavam medidas de prevenção para novos eventos. Esses achados sinalizam que o número de quedas entre idosos pode ser reduzido significantemente se os programas de atenção à saúde ampliarem suas ações apoiando-as no modelo de prevenção de quedas da Organização Mundial de Saúde.
Informal caregivers of older people recovering from surgery for hip fractures caused by a fall: fall prevention
Keywords: Elderly; Accidental falls; Caregivers; Hip fractures; Idoso; Acidente por quedas; Cuidadores; Fraturas de fêmur